ANALISIS KONFIRMATORI EFEKTIVITAS PENYALURAN DANA ZAKAT PRODUKTIF DI BAZNAS KOTA DENPASAR - Aliza Rizki Amalia; Kurniawati; R. Agrosamdhyo (Maisyatuna, 2026)
This study analyzes the effectiveness of zakat distribution by BAZNAS Denpasar City in alleviating poverty. The background shows that although the Productive Zakat program has been implemented, its effectiveness remains limited due to funding constraints linked to the minority Muslim population and minimal government support. This quantitative research uses an ex post facto design and involves 71 mustahik receiving productive zakat, with data collected through questionnaires, observations, and documentation. Data were analyzed using Confirmatory Factor Analysis (CFA) in SPSS 26 to assess validity, reliability, and factors influencing effectiveness. The findings reveal that zakat distribution is carried out through collection, planning, selection, distribution, mentoring, and evaluation stages. The dominant effectiveness factors are target accuracy at 23.457%, program socialization at 17.777%, and goal achievement at 9.356%. Major challenges include limited funding, weak cross-sector collaboration, and restricted information access. Overall, productive zakat is considered fairly effective in improving mustahik independence and contributing to poverty reduction in Denpasar.